Nate expectations - Federle, Tim (Simon & Schuster Books for Young Readers, 2019)
When E.T.: The Musical closes, Nate reluctantly returns home to begin high school and, with his best friend, Libby, makes a project of turning Dickens' Great Expectations into a musical.